IMPLEMENTASI LAYANAN BIMBINGAN DAN KONSELING TERHADAP PEMBENTUKAN KARAKTER SISWA DI SDN SAYABULU KOTA SERANG - Syufriatullailah, Syufriatullailah; Chudari, Ima Ni'mah (Didaktika, 2021)
This research begins with various events in the world of education that are getting lower, and the destruction of moral values that occur in the world of education such as dishonesty and a reduced sense of responsibility, and so on. Departing from these problems SDN Sayabulu tries to shape the character values of elementary school students through guidance and counseling services, the researchers believe that even though there are regulations in primary and secondary schools, the motivation for this research is the lack of tutors, but many elementary schools do not have tutors as the basis for teaching but are conducted by classroom teachers. Teacher behavior is a role model for the teacher as an educator is related to tasks related to supervision and guidance, as well as tasks related to the discipline of students to comply with school regulations and the standard of living of families and communities. This kind of school counseling service is very important in character building, therefore it is necessary to carry out character education efforts in schools, in this school, character building is built by training students, forming Friday customs, and socializing with teachers. This study uses qualitative research methods and case research methods. The research location is SDN Sayabulu, Serang City. The object of this research is the teacher and sixth-grade students. Data collection techniques used in this study indicate that counseling services in class VI SDN Sayabulu Serang City are provided by classroom teachers. The stages taken by the teacher in implementing guidance and counseling services are first, identifying student counseling and determining appropriate guidance. Second, the teacher’s efforts to assist students in solving these problems. The suggestion their enthusiasm, abilities, and abilities in providing counseling services to students, so that they receive the best learning in school.